2011
DOI: 10.1029/2010jd014891
|View full text |Cite
|
Sign up to set email alerts
|

Global radiosonde balloon drift statistics

Abstract: [1] The drift of radiosonde balloons during their ascent has generally been considered a negligible factor in applications involving radiosonde observations. However, several applications envisioned for observations from the Global Climate Observing System (GCOS) Reference Upper Air Network (GRUAN) require estimates of balloon drift. This study presents a comprehensive global climatology of radiosonde balloon drift distance and ascent time, based on 2 years of data from 419 stations, with particular attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 12 publications
(13 reference statements)
4
54
3
Order By: Relevance
“…The observed drifts closely match with the background wind velocities as expected (i.e., the higher the wind velocities, the larger the radiosonde drifts and vice versa). Though we cannot directly compare our results with those reported by Houchi et al (2010) and Seidel et al (2011) (as they have not included any Indian radiosonde observations) on the balloon drifts, note that drifts are larger at our location in contrast to those reported by them. Seidel et al (2011) reported that drifts are larger at mid-latitudes than the tropics, but even at a tropical latitude station like Gadanki, we could notice large drifts.…”
Section: Maximum Horizontal Drift Of the Radiosonde While In Ascent Acontrasting
confidence: 55%
See 2 more Smart Citations
“…The observed drifts closely match with the background wind velocities as expected (i.e., the higher the wind velocities, the larger the radiosonde drifts and vice versa). Though we cannot directly compare our results with those reported by Houchi et al (2010) and Seidel et al (2011) (as they have not included any Indian radiosonde observations) on the balloon drifts, note that drifts are larger at our location in contrast to those reported by them. Seidel et al (2011) reported that drifts are larger at mid-latitudes than the tropics, but even at a tropical latitude station like Gadanki, we could notice large drifts.…”
Section: Maximum Horizontal Drift Of the Radiosonde While In Ascent Acontrasting
confidence: 55%
“…Though we cannot directly compare our results with those reported by Houchi et al (2010) and Seidel et al (2011) (as they have not included any Indian radiosonde observations) on the balloon drifts, note that drifts are larger at our location in contrast to those reported by them. Seidel et al (2011) reported that drifts are larger at mid-latitudes than the tropics, but even at a tropical latitude station like Gadanki, we could notice large drifts. Another striking difference observed is that summer season drifts are larger than winter drifts unlike those reported by Seidel et al (2011).…”
Section: Maximum Horizontal Drift Of the Radiosonde While In Ascent Acontrasting
confidence: 55%
See 1 more Smart Citation
“…GPSRO and radiosonde profiles differ in several ways in terms of measurement characteristics, including profile geometry and horizontal resolution. A radiosonde makes point measurements but balloon drifts an average of 50 km horizontally during the~100 min ascent from the surface to the stratosphere [Seidel et al, 2011]. Although GPSRO profiles have fine vertical resolution (0.5 km in the low troposphere and 1.5 km in the middle atmosphere) by satellite retrieval standards, they have a wide horizontal resolution, ranging from~160 km at the low troposphere to 320 km in the upper atmosphere (i.e.,~250 km, defined by the distance traversed by the radio path as it enters and exits a layer [Kursinski et al, 1997]).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Understanding collocation mismatch is particularly relevant for atmospheric profiles obtained by radiosondes, as the ballons containing the measuring instruments tend to drift uncontrollably from their initial launch position (see [26] and [5]). In particular, collocation mismatch may depend on potential covariates.…”
Section: Introductionmentioning
confidence: 99%